1999
DOI: 10.1046/j.1365-3040.1999.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Wood properties and ring width responses to long‐term atmospheric CO2enrichment in field‐grown loblolly pine (Pinus taedaL.)

Abstract: Loblolly pine (Pinus taeda L.) were grown in the field, under non-limiting nutrient conditions, in open-top chambers for 4 years at ambient CO 2 partial pressures (pCO 2 ) and with a CO 2 -enriched atmosphere (+ 30 Pa pCO 2 compared to ambient concentration). A third replicate of trees were grown without chambers at ambient pCO 2 . Wood anatomy, wood density and tree ring width were analysed using stem wood samples. No significant differences were observed in the cell wall to cell lumen ratio within the latewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 30 publications
(65 reference statements)
4
44
1
2
Order By: Relevance
“…They found an increase in density in wood grown in elevated CO 2 on a poor Podsol soil and a decrease of density under the influence of enhanced nitrogen deposition. Similar to our findings, Telewski et al (1999) found no wood density differences in young Pinus taeda plants grown in elevated and ambient CO 2 . In a comparable study to the one presented here, Ceulemans et al (2002) reported that wood density of P. sylvestris also remained unchanged in elevated CO 2 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They found an increase in density in wood grown in elevated CO 2 on a poor Podsol soil and a decrease of density under the influence of enhanced nitrogen deposition. Similar to our findings, Telewski et al (1999) found no wood density differences in young Pinus taeda plants grown in elevated and ambient CO 2 . In a comparable study to the one presented here, Ceulemans et al (2002) reported that wood density of P. sylvestris also remained unchanged in elevated CO 2 .…”
Section: Discussionsupporting
confidence: 91%
“…They also found that increased N deposition had the opposite effect. In contrast, Rogers et al (1983) and Telewski et al (1999) observed no significant changes in average wood density in Pinus taeda in response to elevated CO 2. To our knowledge, very few studies have compared the mechanical properties directly with morphological and anatomical characteristics.…”
Section: Introductionmentioning
confidence: 72%
“…This observation is supported by idealized 2 3 CO 2 growth experiments where the overall effect on MXD is equivocal, detected inconsistently across species, years, and site characteristics (cf. Hä ttenschwiler et al 1996;Telewski et al 1999;Kilpelä inen et al 2003;Kostiainen et al 2004;Yazaki et al 2005). …”
Section: Resultsmentioning
confidence: 99%
“…A few studies have addressed changes in wood structure caused by elevated [CO 2 ] (Telewski et al 1999;Yazaki et al 2005). Atkinson and Taylor (1996) showed that elevated [CO 2 ] increased vessel diameters in the ring-porous wood of Quercus robur seedlings.…”
Section: Introductionmentioning
confidence: 99%